Efektivitas Penerapan Model Pembelajaran SAVI dan SQ3R terhadap Hasil Belajar IPA Siswa Kelas IV - Septia Ningrum; Sri Sami Asih (Postgraduate, University of Mataram, 2025)
The application of learning models is the factors that influence learning outcomes. This reasearch evaluate how well the SAVI and SQ3R learning models are applied to the scientific learning outcomes of grade IV students at SD Gugus Mensirak in the Belitung Regency. This study uses a single group pretest-posttest model and a pre-experimental research methodology, making it a quantitative study. A sample of 56 students participated in this study: 28 in grade VI of SD Negeri 22 Sijuk who used the SAVI learning model and 28 in grade VI of SD who used the SQ3R learning model. This reasearch used Purposive sampling of the research sample in order to make sure it was appropriate for the study's goals. The results of the computations indicate that the average learning outcomes of students using the SAVI model are 84.14. On the other hand, students' learning outcomes using the SQ3R model average 72.22. The experimental class's n-gain value was 0.65 and the control classes was 0.53, the result is SAVI learning approach outperforms the SQ3R learning model in terms of the science learning outcomes of grade IV students at SD Gugus Mensirak, Belitung Regency, with a 65% increase in student learning outcomes.